Abdominal Wound Problems After Hysterectomy With Electrocautery vs. Scalpel Subcutaneous Incision - David L. Hemsell; Patricia G. Hemsell; Brenda Nobles; Edward R. Johnson; Bertis B. Little; Molly Heard (Hindawi Limited, 1993)
The purpose of this study was to evaluate the relationship between postoperative abdominal incision problems and opening subcutaneous tissues with electrocautery or scalpel. Women scheduled for elective abdominal hysterectomy who gave informed consent were randomly assigned to subcutaneous abdominal wall tissue incision by electrocautery or scalpel. Postoperative abdominal wound problem diagnoses included seroma, hematoma, infection, or dehiscence without identifiable etiology. Fifteen of 380 women (3.9%) developed a wound problem; six had scalpel and nine had electrosurgical subcutaneous incisions (P = 0.4). Thicker subcutaneous tissues (P = 0.04) and concurrent pelvic infection (P < 0.001) were significant risk factors for postoperative wound problems. Only two women (0.5%) developed an infection. We conclude that the method of subcutaneous tissue incision was unrelated to the development of postoperative abdominal incision problems in 380 women undergoing elective abdominal hysterectomy.